Junggo qäšqär tori (2016)
Das ist eine Regierungswebseite der Bezirksregierung des Bezirks Kashgar in Xinjiang der Volksrepublik China. Auf dieser Kategorie dieser Webseite finden sich Beiträge und Informationen über die Geschichte der Kommunistischen Partei Chinas, die Parteitage, die Parteistruktur und die Politik der Kommunistischen Partei Chinas. - This is a government website of the Kashgar District Government in Xinjiang, People's Republic of China. This category of this website contains articles and information about the history of the Chinese Communist Party, the party conventions, the party structure and the policies of the Chinese Communist Party.